A taxonomic study on rafflesia tuan-mudae (rafflesiaceae) in Sarawak - Noor Izah, Binti Shoparwe (Universiti Malaysia Sarawak (UNIMAS), 2013)
RafJlesia tuan-mudae is an endemic species of Sarawak. However, there is a no complete description of R. luanmudae. Field work was done at Gunung Pueh, Gunung Gading and other localities such as Kg. Temurang, Kg. Begu and Lanjak Entimau to sample the blooming R. luan mudae. Detailed measurements and description of R. luanmudae were made. Voucher specimens of R. Illan-mudae from Gunung Pueh was preserved as wet specimen in spirit and deposited at Universiti Malaysia Sarawak Herbarium. Plant DNA materials of unknown Rajjlesia spp. were taken from bracts orland perigone lobe and stored in silica gel. The DNA material was extracted, amplified and sequenced using nuclear ITS region. Maximum Parsimony (MP) and Maximum Likelihood (ML) analyses were carried out to estimate the phylogenetic tree to help in species identification. From the results obtained, it showed that the unknown RafJlesia spp. is closely related to R. luan-mudae based on the Maximum Parsimony and Maximum Likelihood analyses with moderate bootstrap support. From the alignment obtained, it clearly showed that the sequence of the unknown RafJlesia spp. is similar to the known R. Illan-mudae from the GenBank except one mutation at site 787 that differentiate R. luan-mudae with the unknown RafJlesia spp. Therefore, the unknown species could probably be R. luan-mudae. However, more data are needed to confirm this result.